Association of iPACK block and adductor canal block in dogs undergoing the tibial plateau leveling osteotomy technique: Report of 4 cases - da Rosa, Desirée Santos (2024)
Orthopedic procedures are associated with severe postoperative pain. In TPLO, the block commonly used is the sciatic nerve block associated with the femoral nerve block. In orthopedic surgeries in human medicine, the iPACK block associated with the adductor canal block has been used as alternatives that do not affect the strength of the quadriceps femoris muscle. The objective of this study was to evaluate the trans and postoperative analgesic effect of the association of iPACK block and adductor canal block, as well as to evaluate the patient’s motor recovery after surgery. Four patients were selected, without distinction of breed and gender, weighing more than 22lb, referred to TPLO. All patients underwent the combination of iPACK block and adductor canal block with 0.5% bupivacaine. The intraoperative evaluation was carried out by measuring mean arterial pressure, heart rate and respiratory rate, and all patients were stable during the procedure. The postoperative evaluation was carried out based on the assessment of pain using the modified Glasgow scale, in which all patients scored less than 05/24, and assessment of ambulation through videos using the adapted Muzzi scale, presenting ambulation between grade 1 and 2. No patient required intraoperative or postoperative analgesic rescue.